2021
DOI: 10.1111/jwas.12842
|View full text |Cite
|
Sign up to set email alerts
|

A production economic analysis of different stocking density and fry size combinations of milkfish, Chanos chanos, farming in Taiwan

Abstract: Milkfish, Chanos chanos, is often cultured with white shrimp, Penaeus indicus, to maintain ecological stability and increase profits. This study uses the outputs and cost data of 169 milkfish farmers in Taiwan for the years 2018 and 2019 and applies translog cost function modeling to analyze the production scale economy and input-input demand combinations of two stocking densities (<10,000, ≥10,000 fry/ha) and two fry stocking sizes (2-3 in. and ≥4 in.). The study found that high-density stocking (≥10,000 fry/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…According to the results of the Fishermen's Economic Survey by the Taiwan Fisheries Agency, the highest cost associated with milkfish culturing is feed, which accounts for 39.7% of the total cost, followed by labor costs (13.9%), fish fry costs (10.9%), water, electricity and fuel costs (7.5%) and pond servicing costs (2.9%). Referring to the variable settings in studies such as [3], this paper takes four input variables, namely, labor cost, fry cost, feed cost and water, electricity and miscellaneous cost, and two output variables, namely, milkfish production and white shrimp production. The input and output data are converted to the monthly, per-hectare average to be used as the evaluation benchmark.…”
Section: Data Sources and Variables Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the results of the Fishermen's Economic Survey by the Taiwan Fisheries Agency, the highest cost associated with milkfish culturing is feed, which accounts for 39.7% of the total cost, followed by labor costs (13.9%), fish fry costs (10.9%), water, electricity and fuel costs (7.5%) and pond servicing costs (2.9%). Referring to the variable settings in studies such as [3], this paper takes four input variables, namely, labor cost, fry cost, feed cost and water, electricity and miscellaneous cost, and two output variables, namely, milkfish production and white shrimp production. The input and output data are converted to the monthly, per-hectare average to be used as the evaluation benchmark.…”
Section: Data Sources and Variables Definitionsmentioning
confidence: 99%
“…In the early stage, Taiwan's milkfish farming mainly adopted the monoculture method. Later, it was found that a mixed culture with white shrimp (Penaeus indicus) (Figure 2) could not only increase owner's income [1][2][3][4], but also keep fish ponds clean [4][5][6]. However, the cultivation of white shrimp comes with many advantages, such as removing the need for extra feed and cleaning feed residues and fish waste without affecting the growth space needed for milkfish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation